Ideology and Media - Syifaul Arifina, Prahastiwi Utarib dan Sri Hastjarjo (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Haji Misbach is one of the movement figures in Solo known as the idea of Islamiccommunism. Islam and communism are used against capitalism and colonialism.Through the mass media, he delivered a message of resistance. Misbach's writingsin the mass media can be categorized as genre of advocacy and propagandajournalism. Misbach's writing describes a distinctive style of communication.Using Edward T. Hall's theory of intercultural communication, researcher observecommunication style of Misbach. Edward T. Hall stated that communicationstyle is divided into two contexts, namely high context communication(HCC) and low context communication (LCC). this study examines howMisbach's communication style in the print media of Medan Moeslimin and IslamBergerak This is also related to the ideology brought by Misbach..Keywords: ideology, media, Haji Misbach, journalism, communication style